Neonatal pneumococcal meningitis - FZ Mouad; Bennaoui F; N El Idrisi Slitin; N Soraa; FMR Maoulainine (Open Journal of Bacteriology - Peertechz Publications, 2020)
Neonatal pneumococcal meningitis is rare, but serious due to its high mortality and severe psychomotor and neurosensory sequelae.  We report six cases of pneumococcal meningitis collected at the neonatal and neonatal resuscitation department of the CHU Mohamed VI, from January 2014 to July 2020. The aim of our work is to study the peculiarities, clinical, bacteriological, evolutionary of this pathology, and to analyze its transmission during the neonatal period. four patients are aged respectively, one day for one patient, 2 two days for 2 patients and three days for the 4th patient, so the most probable transmission route is transplacental. The other 2 patients were between 6 days and 15 days old, which suggests the probability of exogenous transmission. The clinical picture is variable and atypical, the fever associated with refusal of suckling is found in 100% of patients thus representing the most constant sign. Direct examination of the Cerebrospinal Fluid (CSF) identified the germ in all six cases. The evolution was favorable and the complications are encountered in three patients.